The educational contents derived from the conjunction of the supplications of the Prophets، peace be upon them، with good deeds in the Holy Qur’an and its applications in the family - Thayap, Amal Hmdan (Journal of Educational and Psychological Sciences, 2022)
The research of the educational values deduced from conjugation of the prophets’ supplications, peace be upon them with their righteous deeds in the Qur’an and their applications in the family aims to: Understanding the conceptual framework of research, deducing educational values from the conjugation of prophets' supplications, peace be upon them, is an explicit conjugation with their righteous deeds in the Holy Qur’an as well as deducing educational values from the conjugation of prophets' supplications, peace be upon them, is an implicit conjugation with their righteous deeds in the Holy Qur’an. Furthermore, mentioning the educational applications deduced from attaching the supplications of the prophets, peace be upon them, with their righteous deeds in the Holy Qur’an with regard to the family.
Keywords: Value; conjugation; Pray for; good work; family